2021
DOI: 10.1155/2021/2299632
|View full text |Cite
|
Sign up to set email alerts
|

A Provably Secure Authentication and Key Agreement Protocol in Cloud-Based Smart Healthcare Environments

Abstract: The wide applications of the Internet of Things and cloud computing technologies have driven the development of many industries. With the improvement of living standards, health has become the top priority of people’s attention. The emergence of the wireless body area network (WBAN) enables people to master their physical condition all the time and make it more convenient for patients and doctors to communicate with each other. Doctors can provide real-time online treatment with cloud-based smart healthcare en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This section reviews authentication and key agreement (AKA) protocols [ 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] applied in IoT, cloud computing, and IoT-enabled cloud computing environments. A summary of existing protocols is shown in Table 1 .…”
Section: Related Workmentioning
confidence: 99%
“…This section reviews authentication and key agreement (AKA) protocols [ 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] applied in IoT, cloud computing, and IoT-enabled cloud computing environments. A summary of existing protocols is shown in Table 1 .…”
Section: Related Workmentioning
confidence: 99%
“…As security is the primary concern in many applications like VANETS, IoT, industrial IoT, healthcare industry, and so forth, key agreement plays a vital role in every application, where it can be used in securing sensitive data. Many researchers have proposed key agreements schemes suitable for the applications mentioned above 14–28 . Duncan 29 described many authentication methods and protocols in 2001, beginning with password protection and ending with digital signatures that handle security challenges such as SSL, IPSEC, and Kerberos.…”
Section: Related Workmentioning
confidence: 99%
“…Kumari et al [31] proposed an efficient AKA protocol for smart healthcare and cloud environments, utilizing ECC. However, Wu et al [32] demonstrated that their protocol suffered from several security vulnerabilities, including impersonation, known session specific temporary information (KSSTI), and desynchronization attacks. Subsequently, Wu et al proposed an alternative AKA protocol for smart healthcare, addressing the identified security issues.…”
Section: Introductionmentioning
confidence: 99%